Fabrication of Ti3SiC2-based pastes for screen printing on paper-derived Al2O3 substrates; Ceramics International; Vol. 44, iss. 7 - Carrijo Mylena Mayara Matias; Lorenz Hannes; Rambo C. R. Carlos; Travitsky (Travitzky) N. Nakhum (2018, 2018)
Title screen